2022
DOI: 10.2196/35511
|View full text |Cite
|
Sign up to set email alerts
|

A Photography-based, Social Media Walking Intervention Targeting Autonomous Motivations for Physical Activity: Semistructured Interviews With Older Women

Abstract: Background Older adult women are at risk for negative health outcomes that engaging in sustained physical activity can help prevent. However, promoting long-term maintenance of physical activity in this population has proven to be a challenge. Increasing autonomous motivations (ie, intrinsic, integrated, and identified regulations) for physical activity may facilitate enduring behavior change. Digitally delivered games for health that take a celebratory technology approach, that is, using technolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For instance, a pilot study in United States demonstrated that a social media-based (WeChat) health education was feasible, acceptable, and potentially efficacious in self-management education of older adults with type 2 diabetes [ 21 ]. Another qualitative research found that a photography-based, social media (Facebook) walking game was well received by older women and also benefited for increasing their motivation for physical activity, fostering a shift in perspective, increasing their knowledge, and providing health-related benefits to them [ 22 ]. TikTok, a platform for sharing short videos, has been phenomenal since the onset of the COVID-19 pandemic and has reached Chinese seniors [ 23 ] by providing simple video-editing tools [ 24 ] and catering to specific informational and practical needs [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a pilot study in United States demonstrated that a social media-based (WeChat) health education was feasible, acceptable, and potentially efficacious in self-management education of older adults with type 2 diabetes [ 21 ]. Another qualitative research found that a photography-based, social media (Facebook) walking game was well received by older women and also benefited for increasing their motivation for physical activity, fostering a shift in perspective, increasing their knowledge, and providing health-related benefits to them [ 22 ]. TikTok, a platform for sharing short videos, has been phenomenal since the onset of the COVID-19 pandemic and has reached Chinese seniors [ 23 ] by providing simple video-editing tools [ 24 ] and catering to specific informational and practical needs [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some types of social media have been proven to be effective in medical studies to disseminate health knowledge or improve behaviour, such as Twitter, Facebook, Instagram, TikTok, WeChat, Weibo [29][30][31][32][33][34] . More importantly, a number of studies have demonstrated that older populations are receptive to social media as a tool for knowledge dissemination or health intervention [35][36][37][38] . Particularly, TikTok, a platform for sharing short videos, has been phenomenal since the onset of the COVID-19 pandemic and has reached Chinese seniors 39 by providing simple videoediting tools 40 and catering to specific informational and practical needs 41,42 .…”
Section: Introductionmentioning
confidence: 99%